Tumor microenvironment-induced tumor cell plasticity: relationship with hypoxic stress and impact on tumor resistance - Zaarour, RF.; Ribeiro, M.; Azzarone, B.; Kapoor, S.; Chouaib, S. (Frontiers in Oncology, 2023)
The role of tumor interaction with stromal components during carcinogenesis is crucial for the design of efficient cancer treatment approaches. It is widely admitted that tumor hypoxic stress is associated with tumor aggressiveness and thus impacts susceptibility and resistance to different types of treatments. Notable biological processes that hypoxia functions in include its regulation of tumor heterogeneity and plasticity. While hypoxia has been reported as a major player in tumor survival and dissemination regulation, the significance of hypoxia inducible factors in cancer stem cell development remains poorly understood. Several reports indicate that the emergence of cancer stem cells in addition to their phenotype and function within a hypoxic tumor microenvironment impacts cancer progression. In this respect, evidence showed that cancer stem cells are key elements of intratumoral heterogeneity and more importantly are responsible for tumor relapse and escape to treatments. This paper briefly reviews our current knowledge of the interaction between tumor hypoxic stress and its role in stemness acquisition and maintenance. Our review extensively covers the influence of hypoxia on the formation and maintenance of cancer stem cells and discusses the potential of targeting hypoxia-induced alterations in the expression and function of the so far known stem cell markers in cancer therapy approaches. We believe that a better and integrated understanding of the effect of hypoxia on stemness during carcinogenesis might lead to new strategies for exploiting hypoxia-associated pathways and their targeting in the clinical setting in order to overcome resistance mechanisms. More importantly, at the present time, efforts are oriented towards the design of innovative therapeutical approaches that specifically target cancer stem cells.